Nghiên cứu các giải pháp giáo dục trẻ em lang thang Việt Nam - Phạm, Đức Quang (2011)
Tác giả: Phạm Đức Quang, TS; Chu Ngọc Bảo, KS; Nguyễn Thị Khoa, TS; Trịnh Ngọc Tân, ThS; Đăng Thị Hòe, ThS -- Từ khóa: Trẻ lang thang; Giáo dục; Trẻ em đường phố